DYNAMICS OF THE MARINE FAUNAL DIVERSITY IN THE PHANEROZOIC: A NEW APPROACH - Markov A.V. (My University, 2001)
The dynamics of the marine faunal diversity in the Phanerozoic are analyzed on the basis of the total duration of genera (D). The diagramatic representation of D is more regular and thus easier to interpret than the well-known curve of the number of genera (NG). Four periods when D increased at constant rates are identified. These periods of linear growth are separated by crisis periods. The constant rates of D form a rather strict geometric progression. This progression is the first quantitative pattern in the dynamics of the marine faunal diversity of the Phanerozoic that is obeyed so accurately.